Globalization East and West - Turner, Bryan S.; Khondker, Habibul Haque; SAGE Knowledge (Online service). (Thousand Oaks, Calif. Sage, 2010)
"Do we confuse globalization for Americanization? What are the distinctive elements in the interplay of the local and the global?This much needed book is the first full length text to examine globalization from the perspective of both the West and the East. It considers globalization as a general social and economic process, and the challenges it presents for Western social science. The meaning of a global perspective is explored through various concrete examples: religion, migration, medicine, terrorism, global disasters, citizenship, multiculturalism, media and popular culture. Introduced with a forward from Roland Robertson the book is brimming with novel interpretations and fresh insights that will contribute to illuminating the practical realities of globalization."-Provided by publisher.
Prospects for a New Sociology of Globalization -- Conceptualizing Globalization -- Structures and Processes of Globalization -- Globalization and the Nation-State -- Globalization, Culture and Cosmopolitanism -- World Religions and Fundamentalism -- Migration and Transnationalism -- Medical Globalization -- New Wars and Terrorism: Globalization of Militarism and Violence -- Globalization of Disasters and Disaster Response -- Globalization, Citizenship and Human Rights -- Multiculturalism, Social Diversity and Globalization -- Religion, Media and Popular Culture.
Includes bibliographical references (p. [219]-229) and index.
Keywords: Globalization; Comparative government; East and West; Electronic books